Mama Guaco y Chañan Cori Coca: un arquetipo o dos mujeres de la Historia Inca. (Reflexiones sobre la iconografía de un cuadro del Museo de la Universidad de San Antonio Abad del Cuzco) - Ramos Gómez, Luis (Revista Española de Antropología Americana, 2001)
Analyzing a picture of the XVIII century, we identificated his protagonists —the chanca people, Mama Guaco y Chañan Cori Coca— using historical and iconographical data about Incas and colonial Andean-Hispanic culture.